2012
DOI: 10.5194/nhess-12-287-2012
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication "Seismic and acoustic-gravity signals from the source of the 2004 Indian Ocean Tsunami"

Abstract: Abstract. The great Sumatra-Andaman earthquake of 26 December 2004 caused seismic waves propagating through the solid Earth, tsunami waves propagating through the ocean and infrasound or acoustic-gravity waves propagating through the atmosphere. Since the infrasound wave travels faster than its associated tsunami, it is for warning purposes very intriguing to study the possibility of infrasound generation directly at the earthquake source. Garces et al. (2005) and Le emphasized that infrasound was generated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…It is to be mentioned here that similar observations of low-frequency atmospheric waves have been recorded after three megathrust events, since the 1964 Alaskan earthquake (Mw = 9.2) [16,17], the 2004 Sumatra-Andaman earthquake (Mw = 9.2) [18,19], and the 2011 great Off-Tohoku earthquake (Mw = 9.0) [20,21]. In the present article, we try to find the evidence of observations for low-frequency gravity waves propagating from each of the source regions of the above two great earthquakes through the atmosphere to some of these microbarograph stations.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is to be mentioned here that similar observations of low-frequency atmospheric waves have been recorded after three megathrust events, since the 1964 Alaskan earthquake (Mw = 9.2) [16,17], the 2004 Sumatra-Andaman earthquake (Mw = 9.2) [18,19], and the 2011 great Off-Tohoku earthquake (Mw = 9.0) [20,21]. In the present article, we try to find the evidence of observations for low-frequency gravity waves propagating from each of the source regions of the above two great earthquakes through the atmosphere to some of these microbarograph stations.…”
Section: Introductionsupporting
confidence: 75%
“…For these possible reasons, we did not make further attempts to fit exactly the calculated amplitudes to their corresponding observations. We would like to mention here that these are the fourth and fifth megathrust earthquakes, from which lowfrequency atmospheric waves including gravity modes have been emitted, since the first, unusual observation after the 1964 Alaskan earthquake (Mw = 9.2) [16,17], the Sumatra-Andaman earthquake (Mw=9.2) [18,19], and the 2011 OffTohoku earthquake (Mw=9.0) [21].…”
Section: Resultsmentioning
confidence: 99%
“…This difference may result in a very useful tsunami warning time. Mikumo et al (2008) and Raveloson et al (2011) identified acoustic-gravity waves with periods of about 500 s caused by the great 2004 Sumatra-Andaman earthquake and used them to estimate the dislocation of the sea level in the source region.…”
Section: Introductionmentioning
confidence: 99%